The Effect Of Supervision On Employee Performance At PT Bank Sumut Syariah Padangsidimpuan Branch - Hilman Saleh Daulay; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
The purpose of this research is to determine and analyze the effect of supervision on employee performance at PT Bank Sumut Syariah Padangsidimpuan Branch. This research was carried out at PT Bank Sumut Syariah Padangsidimpuan Branch. The type of research is associative quantitative. The sample in this study was 22 employees with ASN and honorary status at PT Bank Sumut Syariah Padangsidimpuan Branch. The sampling technique in this study used the entire population of 22 people. The research results show that supervision has a significant influence on employee performance as shown by the T-Statistic value of 8.716 > 1.753 and the P value of 0.000 < 0.05. This shows that improvements in Supervision can improve employee performance at PT Bank Sumut Syariah Padangsidimpuan Branch.